Instilling The Value of Multiculturalism Based on The Quran and The Huma Betang Philosophy - Aulia Kiftiah; Ahmadi; Ajahari (Mudir: Jurnal Manajemen Pendidikan, 2025)
This study aims to instill the values ​​of multiculturalism based on the Qur'an and the philosophy of Huma Betang in the context of a multicultural Indonesian society. The method used is a literature study, which involves collecting and analyzing data from various written sources, including books, articles, and scientific journals. The results of the study indicate that multiculturalism in Indonesia, which is reflected in the motto "Bhinneka Tunggal Ika," requires recognition and appreciation of differences to create a harmonious society. From an Islamic perspective, the values ​​of tolerance and mutual respect taught in the Qur'an, as well as the local wisdom of Huma Betang, can be the foundation for overcoming intolerance. This study concludes that the integration of these values ​​can strengthen social cohesion and encourage religious moderation, which is important in facing the challenges of intolerance and radicalization in the era of disruption. Instilling the values ​​of multiculturalism based on the Qur'an and the philosophy of Huma Betang is expected to create a more peaceful and tolerant society in Indonesia.